(untitled) (REMUNOM, 2026)
The increasing incidence of chronic and progressive diseases that threaten life has consolidated the importance of Palliative Care (PC). This approach aims at preventing and alleviating suffering through early identification, assessment, and impeccable treatment of pain and other problems of a physical, psychosocial, and spiritual nature. The central philosophy of PC is the promotion of quality of life and dignity, regardless of the stage of the disease. This study aims to: Describe the relevance and main interventions of the stoma therapist nurse in the planning and execution of nursing care for patients in palliative care with infected wounds. The justification for this study lies in the need to highlight the importance of integrating knowledge of Stoma Therapy into the context of Palliative Care. It is hoped that this analysis will contribute to raising awareness among managers and health professionals about the need to include the stoma therapist in PC teams, promoting comprehensive, humanized, and evidence-based care. This is an integrative literature review study, a method that allows the search, evaluation, and synthesis of significant scientific evidence on a specific topic. This approach allows the gathering of data from studies with diverse methodologies (quantitative and qualitative). To select the articles, a search was conducted in the following databases: National Library of Medicine (PubMed), Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and BDENF via the Virtual Health Library in Nursing (BVS), Google Scholar, and Scientific Electronic Library Online (SciELO). To consolidate the analyzed data, thematic categories were developed, namely: The role of the stoma therapist in the assessment and treatment of infected wounds in palliative care; Nursing care for patients in palliative care with infected wounds; Essential nursing interventions in the management of infection and symptoms; Psychosocial support, communication, and innovative approaches in palliative care; The approach of the stoma therapist: a differential in care; Symptom management and comfort-centered care for patients in palliative care; The role of the stoma therapist in the assessment and treatment of infected wounds in palliative care and the role of the stoma therapist nurse in advanced approaches to infected wounds. In conclusion, the stoma therapist plays an essential role in the care of patients in palliative care with infected wounds, acting both in clinical assessment and in the advanced management of these lesions. Their practice is oriented towards comfort, symptom control, and improvement of quality of life, fundamental principles of palliative care. Therefore, the stoma therapist’s work stands out for its technical expertise and specialized approach, allowing for a detailed assessment of each type of infected wound and the application of advanced interventions according to the complexity of each case.